1994
DOI: 10.1007/bf00306818
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of traumatic extradural hematoma: a comparison between children and adults

Abstract: In this study of 43 children who had surgery for traumatic extradural hematoma (EDH) at Frenchay Hospital, England, between 1975 and 1987, the authors attempt to outline the various clinical characteristics of EDH which are different in children (age range 1-15 years) and adults (age range 16-84 years). The results confirm that children with traumatic EDH are less likely to have injury be caused by an RTA, are less likely to remain unconscious from the time of injury to the time of the operation, and are less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
3
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 16 publications
7
23
3
5
Order By: Relevance
“…Similar results have been reported by other authors (14,20,23,24,27) but Dhellemmes found that 64% patients with EDH had been involved RTA and other causes had occurred less frequently (11). RTA is the commonest mode of injury in adult also (9,16). So, this series showed a significant difference in the mechanism of injury between children and adults.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results have been reported by other authors (14,20,23,24,27) but Dhellemmes found that 64% patients with EDH had been involved RTA and other causes had occurred less frequently (11). RTA is the commonest mode of injury in adult also (9,16). So, this series showed a significant difference in the mechanism of injury between children and adults.…”
Section: Discussionsupporting
confidence: 90%
“…Traumatic extradural haematoma (EDH) in children accounted for 12 % of the 1460 patients with an epidural hematoma operated in our institution in the same period. This lower incidence of acute epidural hematoma in the children compared with adults is also reported in other series and is attributable to the tight adherence of the dura mater to the inner table of the skull (11,16,24,27). In our series, the age of the patients ranged from 1.8 years to 18 years with a mean age of 9.49 years.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has been estimated that EDH represents 2-3% of all head injuries in the pediatric population . 3 The mean age of pediatric patients harboring EDH is between 6 and 10 years and EDH is even rarer among infants under the age of 12 months 2 -5. It is recognized that EDH in children differ from EDH in adults in that the haematoma may follow a trivial injury, the symptoms are different, the course is more insidious, associated skull fracture is infrequent 6 and this make it difficult to diagnose and often challenging to manage. Furthermore, the criteria for utilizing surgical evacuation vs conservative management have remained ill-defined.…”
Section: Introductionmentioning
confidence: 99%